Uji Coba Sistem Penilaian Kinerja Karyawan dengan Metode Behaviorally Anchor Rating Scale di PT X - Nabila Putri Mahadewi; Nindiya Rindhi Ashifa (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Performance assessment is very important for a company when it comes to making decisions. Performance assessment can also affect employee motivation and commitment at work and can affect the criteria for promotion. In general, some companies use a performance assessment system that is subjective and is considered less effective because there is no standard, making employees feel less fair in terms of assessment. To overcome these problems, it is necessary to design an assessment system with the Behaviorally Anchor Rating Scale (BARS) method because this method is more objective in matters that need to be assessed. It is hoped that this BARS method can assess all employees more objectively and fairly and can affect the motivation of employees to be more active in work.